Hukum Sebagai Insrumen Untuk Mencapai Tujuan Negara serta Menggerakkan Perubahan terhadap Masyarakat - Deana Zahirah; Raina Nadheera (Universitas Sains dan Teknologi Komputer, 2023)
Termination of employment often triggers industrial relations conflicts between workers and employers, conflicts between the two parties occur because of disputes over the amount of proper severance pay, long service pay, compensation money and so on. As stated in the Minister of Manpower Regulation number 14 of 2020 concerning guidelines for providing government assistance in the form of salary/wages subsidies, Article 1 paragraph (3) which states